Failure Analysis of the Clutch Brake System in a 400-ton Hyundai Stamping Press - Muhammad Firdausi; Rafie Safa Mahendra (International Journal of Advanced Multidisciplinary, 2026)
Stamping press machines rely on reliable clutch brake systems to ensure operational accuracy, productivity, and safety. This study presents an empirical failure analysis of a wet-type multi-disc clutch brake system in a 400-ton stamping press that experienced operational failure following flood exposure. Field observations, visual and dimensional inspections, and hydraulic system evaluations were conducted to identify failure mechanisms and root causes. The results indicate that the clutch brake failure was caused by the combined effects of mechanical interference leading to hydraulic hose rupture, improper installation of sealing components, and aging-related degradation of elastomeric seals. Flood-induced contamination significantly accelerated lubrication failure and material deterioration, resulting in hydraulic leakage and loss of system reliability. Corrective actions, including component replacement, lubrication system restoration, and hydraulic pressure adjustment, were implemented and validated through no-load testing, load testing, and production trials using actual stamped parts. Post-repair testing confirmed stable machine operation and acceptable product quality. The novelty of this study lies in demonstrating how environmental exposure interacts with installation errors and material aging to produce system-level clutch brake failure. The findings provide practical guidance for failure prevention, condition-based maintenance, and reliability improvement of heavy-duty stamping press machines operating in flood-prone industrial environments.